Effect of fermentation on water mobility and distribution in fermented cornmeal using LF-NMR and its correlation with substrate - Yang, Shuang (J Food Sci Technol, 2019)
Cordyceps militaris (C. militaris) was utilized to ferment cornmeal by solid state fermentation. The main objective of this study was to investigate effect of fermentation on the dynamic state of water and microstructure distribution of water within cornmeal with Low-field nuclear magnetic resonance, as well as the effect on composition and microstructure properties. The spin–spin relaxation time (T(2)) showed significant changes in solid-state fermented cornmeal. Principal component analysis further revealed that the variations within different fermentation stage could be discriminated by the T(2) parameters. Bulk water (T(22)) was the main form of water present and lost in substrates. The weights of different indicators, as assessed by multiple regression analysis, demonstrated that there was a strong correlation between starch and T(2) relaxation. Scanning electron microscopy demonstrated that fermentation can cause the appearance of micropores. The longer relaxation time of T(22) during logarithmic period can be interpreted as a loosening of the structure at the starch hydrolysis, introducing more water into the structure. Thus, the differences in composition and structure of the substrate at different fermentation time produce different T(2) values. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-019-03569-0) contains supplementary material, which is available to authorized users.